2018
DOI: 10.1002/rnc.4058
|View full text |Cite
|
Sign up to set email alerts
|

Sliding mode control design using canonical homogeneous norm

Abstract: Summary The problem of sliding mode control design for a nonlinear plant is studied. The necessary and sufficient conditions of quadratic‐like stability (stabilizability) for a nonlinear homogeneous (control) system are obtained. Sufficient conditions of robust stability/stabilizability are deduced. The results are supported with academic examples of sliding mode control design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
151
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(152 citation statements)
references
References 45 publications
1
151
0
Order By: Relevance
“…It is shown that any generalized homogeneous finite-time stable system admits implicit Euler discretization preserving finite-time convergence. The topological equivalence [29] of homogeneous stable system to a quadratically stable one is utilized for the design of this scheme. Theoretical results are supported with numerical simulations.…”
Section: Finite-time Stable Implicit Discretizationmentioning
confidence: 99%
“…It is shown that any generalized homogeneous finite-time stable system admits implicit Euler discretization preserving finite-time convergence. The topological equivalence [29] of homogeneous stable system to a quadratically stable one is utilized for the design of this scheme. Theoretical results are supported with numerical simulations.…”
Section: Finite-time Stable Implicit Discretizationmentioning
confidence: 99%
“…Definition 5 [9], [5] The dilation d is said to be strictly monotone if ∃β such that d(s) A ≤ e βs for s ≤ 0.…”
Section: B Generalized Homogeneitymentioning
confidence: 99%
“…In particular, local stability of homogeneous system means the global one; if an asymptotically stable system is homogeneous with negative degree, then it is finitetime stable, etc. The present paper deals with generalized homogeneity [12], [5], which is based on groups of linear transformations (linear dilations).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] The passive FTC does not require fault detection and diagnostic scheme, and the controllers are designed to be robust against a class of presumed faults. [8][9][10][11][12][13][14] Sliding mode control (SMC) techniques are widely exploited not only in theory but also in practical applications [15][16][17][18][19][20] due to its strong robustness. In the work of Xu et al, 21,22 the FTC approach based on terminal sliding-mode method was presented for finite-time attitude stabilization of satellite, which also resolved the potential singularity problem of traditional terminal SMC designs.…”
Section: Introductionmentioning
confidence: 99%